(untitled) (Health and Biosciences, 2025)
Over the past four decades, advances in molecular biology have transformed the role of viruses, shifting them from a commonly assigned “villain” role to key players in sophisticated therapeutic strategies. Viral vector-based gene therapy arises from the detailed study of these organisms, combined with continuous improvements in molecular biology techniques, aiming to expand the therapeutic scope for conditions closely linked to genetic dysfunctions and infectious diseases lacking effective conventional treatments. Gene therapy introduces a new paradigm in vaccine development: genetic vaccines, which, by exploiting complex gene transfer and regulation mechanisms, can induce not only specific immune responses but also systemic and intricate physiological changes, broadening therapeutic approaches for various diseases. This review aims to consolidate fundamental virological knowledge supporting the use of viruses in gene therapy, as well as to present the most prominent viral vectors employed to date and their respective clinical applications.